Pengaruh Etika dan Kompetensi terhadap Kinerja Pegawai pada Kantor Kecamatan Sematang Borang Kota Palembang - Rohmial , Rohmial (Catholic University Musi Charitas, 2021)
The objectives of this study are 1). to examine the effect of ethics on employee performance atthe Sematang Borang District Office. 2). to test the effect of employee competence onemployee performance at the Sematang Borang District office, 3). to examine the effect ofethics and employee competence on employee performance at the Sematang Borang Districtoffice. This research was conducted on 31 employees at the Sematang Boran sub-districtoffice in Palembang City using a questionnaire. A questionnaire consisting of Ethicalvariables and employee competence as independent variables and employee performance asthe dependent variable. This study uses simple regression analysis and multiple linearregression to see which variables are more influential and the size of the contribution of eachvariable in influencing performance. It is hoped that this research will contribute toemployees regarding the importance of ethics and competence in serving the community, sothat employee performance is maximized. The results of this study indicate that the variablesof ethics and employee competence have a significant effect on the performance of employees at the Head Office of Sematang Borang, Palembang City.